2015
DOI: 10.1016/j.corsci.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the effect of surface roughness on the oxidation of Zircaloy-4

Abstract: a b s t r a c tZirconium alloys are used as fuel cladding in light water reactors. Surface preparation techniques that might impair oxidation resistance would limit the lifetime of the cladding and therefore prevent higher burn-up of fuels. The work presented here investigates the impact of surface roughness on the oxidation kinetics of Zircaloy-4 in 400 • C steam for exposures up to 275 days. The work shows well defined differences in oxidation kinetics between sample preparations following ∼84 days oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
6
22
0
Order By: Relevance
“…This work determines the fracture strength of oxides formed thermally on zirconium alloys, and offers a route to investigate other thin films and coatings. It also demonstrates the potential impact of the surface roughness in promoting fracture of the oxide layer, which could reduce the protective nature of the oxide layer [44].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This work determines the fracture strength of oxides formed thermally on zirconium alloys, and offers a route to investigate other thin films and coatings. It also demonstrates the potential impact of the surface roughness in promoting fracture of the oxide layer, which could reduce the protective nature of the oxide layer [44].…”
Section: Discussionmentioning
confidence: 96%
“…These include the impact of initial surface roughness [44], interfacial roughness which develops during oxidation [7,[15][16][17]45], and the tetragonal to monoclinic phase transformation [20,46]. These cracks have been directly linked with breakdown of the protective character of the oxide and acceleration in the corrosion kinetics, via the creation of fast ingress routes for oxygen containing species [7,11,12,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Cl -and Cl2 diffuse through the oxide grain boundaries ("electrochemical" mechanism) and oxide's defects ("active-corrosion" mechanism) respectively to reach the coating/oxide scale interface. Vaporization of the metallic chlorides occurs in this step, which leads to formation of the gap at the coating/chloride layer [45]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The previous work performed in an ambient air environment at 600 °C for 168 h indicated that reducing the surface roughness to Ra<0.1 μm resulted in the weight gain of the NiCrMoSiO2 coating being reduced by ~71% compared to the non-polished coating. Such behavior could be attributed to either the higher level of residual stresses (above the roughness peaks) which lead to oxide spallation/cracking, or higher surfcae area exposed to the environment in the as-spryaed coatings [45]. Fig.…”
Section: Surface Morphology Cross Section and Xrd Analysis Of As-spmentioning
confidence: 99%
“…In oxides formed on zirconium alloys cracks are known to form parallel and close to the metal oxide interface (N. P Platt et al, 2015;P. Platt et al, 2015a), and perpendicular to the metal-oxide interface at higher temperatures (Omar et al, 2015;Parry et al, 2013).…”
Section: Damage Analysismentioning
confidence: 99%